ChemInform Abstract: A Palladium‐Catalyzed Carbonylation Approach to Eight‐Membered Lactam Derivatives with Antitumor Activity. Issue 28 (June 2016) - Mancuso, Raffaella; Raut, Dnyaneshwar S.; Marino, Nadia; De Luca, Giorgio; Giordano, Cinzia; Catalano, Stefania; Barone, Ines; Ando, Sebastiano; Gabriele, Bartolo
Abstract: Aniline substrates such as (I) and (V) bearing a terminal acetylene at the phenoxy part are suitable for the preparation of the target compounds in the presence of CO and alcohols under conditions A).